Cow urine spray and integrated nutrient management of rice on productivity and energy-use under temperate valley conditions - Singh, Lal; Singh, Parmeet; Kotru, Rajinder; Hasan, Badrul; Chand, Lekh; Lone, B A (The Indian Journal of Agricultural Sciences, 2012)
Cow urine as a nutrient source to rice crop was evaluated in field experiments conducted during rainy (kharif) seasons of 2008 and 2009 at the Agronomy Research Field, Shalimar, Srinagar. The maximum plant height, effective tillers/hill, filled grains/panicle, grain yield and straw yield were noticed with application of 15 tonnes FYM + 120:60:30 kg N:P2O5:K2O/ha, which was significantly superior to rest of the treatments except plant height and straw yield, which were at par with 15 tonnes FYM + 60:60:30 kg N:P2O5:K2O/ha in 2008 and plant height with 15 tonnes FYM + 60:60:30 kg N:P2O5:K2O/ha and 15 tonnes FYM /ha in 2009. The maximum uptake of N, P and K was recorded with application of 15 tonnes FYM + 120:60:30 kg N:P2O5:K2O/ha than rest other treatments during both the years. In case of fresh cow urine and Neemuch mutka khad, three spray of both shows significantly higher N, P and K uptake and grain yield in comparison to two sprays. However, Neemuch mutka khad recorded higher uptake than fresh cow urine. The application of FYM with inorganic fertilizer significantly improved final N, P and K status of soil. Integrated use of 15 tonnes FYM + 120:60:30 kg N:P2O5:K2O/ha recorded maximum net returns (` 20 650/ha) and net energy output (189 386.1 MJ/ha). However, B:C ratio (0.61), energy output : input ratio (26.61) and energy use efficiency (0.85 kg grains/MJ) and (2.06 kg dry matter/MJ) were computed higher under control (no nutrient application). Minimum B:C ratio was observed under application of FYM alone than rest other treatments during both the years. Three spray of fresh cow urine and Neemuch mutka khad were shown superiority over two spray in terms of B:C ratio, energy output : input ratio and energy-use efficiency.